Synthesis of palmyrolide A and its cis-isomer and mechanistic insight into trans-cis isomerisation of the enamide macrocycle - Philkhana, Satish Chandra; Seetharamsingh, B.; Dangat, Yuvraj B.; Vanka, Kumar; Reddy, D. Srinivasa (Chemical Communications, 2013)
Concise and protecting-group free synthesis of ent-palmyrolide A and (-)-cis-palmyrolide A were achieved starting from commercially available (S)-citronellal. The key fragment of palmyrolide A, ``(5S,7S)-7-hydroxy-5,8,8-trimethylnonanamide'', which makes up the most challenging part of the target molecule, was prepared in just three steps. A plausible mechanism for the trans-cis isomerization of the double bond in the macrocycle has been investigated.

Synthesis and biological evaluation of palmyrolide a macrocycles as sodium channel blockers towards neuroprotection - Philkhana, Satish Chandra; Mehrotra, Suneet; Murray, Thomas F.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2016)
Palmyrolide A is a neuroprotective macrolide isolated by Gerwick and coworkers in 2010. This natural product is known to suppress neuronal spontaneous calcium ion oscillations through its voltage-gated sodium channel blocking ability which is of significant interest in CNS drug discovery. Herein, we give a detailed account on total synthesis of (+)-palmyrolide A and synthesis of a focused library of macrocycles around the scaffold, followed by their biological evaluation. Use of the chiral pool approach, Zhu's oxidative homologation, access to unnatural cis-palmyrolide A, preparation of 18 new analogues and identification of macrolides with improved sodium channel blocking activity are the important features of the present paper. As a measure of potency as voltage-gated sodium channel blockers, all the synthesized analogues were profiled for their ability to inhibit the veratridine-stimulated Na+ influx in murine primary neuronal cultures. Four macrocycles were found to be more potent or comparable to that of the natural product (-)-palmyrolide A. The most potent compound from this series 20 was structurally simplified and readily accessible in good quantities for further biological profiling.